Rekomendasi Penerima Bantuan Siswa Miskin (BSM) dengan Metode Simple Additive Weighting (SAW). Studi Kasus : SMP N 1 Lintongnihuta - Denni M Rajagukguk (Yayasan Kita Menulis, 2019)
The BSM Program is a National Program that aims to remove barriers to poor students from participating in school by helping poor students to get access to appropriate education services, preventing dropouts, attracting poor students to return to school, helping students meet needs in learning activities, supporting Mandatory programs Learning Nine-year Basic Education (even to the senior secondary level), and helping the smooth running of school programs. Through this BSM program it is hoped that school-age children from poor households / families can continue to go to school, not dropping out of school, and in the future they are expected to break the poverty chain currently experienced by their parents. The BSM program also supports the government's commitment to increase education participation rates in poor and remote regencies / cities and marginalized groups. In essence the simple additive weighting (SAW) method is often also known as the weighted sum method. The basic concept of the simple additive weighting (SAW) method is to find the weighted sum of the performance ratings for each alternative on all attributes. The simple additive weighting (SAW) method requires the decision matrix normalization process.